Mononeuritis Multiplex Associated With Antiphospholipid Antibodies - Luis Francisco VALDÉS CORONA; Alejandro DÍAZ BORJÓN (Archives of Rheumatology, 2020)
In this article, we report the case of a 43-year-old male patient with mononeuritis multiplex associated with antiphospholipid antibodies. The patient had no other clinical or laboratory features of other systemic or autoimmune diseases or systemic vasculitis. He was treated with oral anticoagulant and mycophenolate mofetil, and is progressing favorably.